NEUROTIC DISORDERS AND THEIR CAUSES AND CONSEQUENCES IN WOMEN - Bekmirov Tolib Rashidovich (Bright Mind Publishing, 2025)
This article provides information about the specifics of neurotic states in women and the disease of neurosis. The world's leading psychologists have covered the specifics of neurotic states in women and drawn conclusions.
Keywords: Neurosis. Neurotic states. Psychoemotional state. Psychotherapy.